Kratom Use Within the Context of the Evolving Opioid Crisis and the COVID-19 Pandemic in the United States - Prozialeck, Walter C.; Lamar, Peter C.; Krupp, Michael; Moon, Matthew; Phelps, Laura E.; Grundmann, Oliver (Frontiers in Pharmacology, 2021)
Abstract Kratom (Mitragyna speciosa, Korth.) is an evergreen tree that is indigenous to Southeast Asia. When ingested, kratom leaves or decoctions from the leaves have been reported to produce complex stimulant and opioid-like effects. For generations, native populations in Southeast Asia have used kratom products to stave off fatigue, improve mood and alleviate pain and symptoms of opioid withdrawal. Despite the long history of kratom use in Asia, it is only within the past 10-20 years that kratom has emerged as an important herbal agent in the United States, where it is being used for the self-treatment of pain, opioid withdrawal symptoms and mood disorders. The increase in the use of kratom in the United States has coincided with the serious epidemic of opioid abuse and dependence. Since 2015, efforts to restrict access to prescription opioids have resulted in a marked increase in the use of “street” opioids such as heroin and illicit fentanyl. At the same time, many patients with chronic pain conditions or opioid use disorder have been denied access to appropriate medical help. The lack of access to care for patients with chronic pain and opioid use disorder has been magnified by the emergence of the COVID-19 pandemic. In this report, we highlight how these converging factors have led to a surge in interest in kratom as a potential harm reduction agent in the treatment of pain and opioid use disorder.